Selection of Potential Bacteria in Termite Nest and Gut for Sustainable Agriculture - Kunhachan, Phanukit; Sirithana, Wandee; Komutiban, Orapin; Limkhuansuwan, Vassanasak; Menchai, Phanchai; Trakunjae, Chanaporn; Lomthong, Thanasak; Ruchusatsawat, Kriangsak; Samaimai, Srisuda (Trends in Sciences, 2024)
In this study, bacteria with the best abilities in cellulose degradation, siderophore production, phosphate solubility, and Pythium parasitica inhibition were selected from termite nests and guts. The isolate BTNASP 5-2, BTPK 5-3 and BTNA 5-1 from termite guts exhibited highest in siderophore production index (SPI) (4.16 ± 0.21), phosphate solubilizing index (PSI) (2.10 ± 0.14) and percentage inhibition of radial growth (PIRG) (67.07 ± 4.02 %), respectively. The BGNACMC 4-3 isolated from termite nest gave the highest cellulolytic index (CI) of 5.17 ± 0.24. Bacterial classification was performed using 16s rRNA gene sequencing. The isolates BTPK 5-3, BGNACMC 4-3 and BTNA 5-1 were found closely related to Bacillus cereus, whereas the bacterial isolate BTNASP 5-2 was closely related to Bacillus subtilis. It is also suggested that the Bacillus cereus exhibited a variety of biological activities, denoting the highest cellulase, phosphate-solubilizing and antifungal activities, while Bacillus subtilis produced only a siderophore. The results obtained suggest that the bacteria selected will be used to develop bio-compost to promote plant growth, leading to sustainable farming. HIGHLIGHTS Bacillus cereus exhibited a variety of biological activities, denoting the highest cellulase, phosphate-solubilizing, and antifungal activities Bacillus subtilis produced a siderophore The highest cellulose-degrading bacteria ( cereus BGNACMC4-3) found in termite mound nest GRAPHICAL ABSTRACT